Ratio of End-Systolic Volume to Left Atrial Area Is a Solid Benchmark of Systolic Dysfunction in Non-Ischemic Cardiomyopathies - Boban, Marko (Med Sci Monit, 2018)
BACKGROUND: Impairment of systolic function and late gadolinium enhancement (LGE) are well-known negative prognostic markers in non-ischemic cardiomyopathies (NICMPs). There is limited knowledge of the geometrical rearrangements of the ventricle volumes over size of the left atrium and their connections with systolic dysfunction and existence of LGE. MATERIAL/METHODS: Consecutive cases of NICMPs with impaired systolic function and controls were included from a computerized database of cardiac magnetic resonance exams for a 2.5-year period. Ratios made from volumetric parameters over left atrial area (LAA) area were calculated. RESULTS: Our study included 205 cases referred to cardiac magnetic resonance (CMR); age was 48.7±17.0 years (range 15.2–80.4), male-to-female ratio 137 (66.8%): 68 (33.2%), (both p>0.05). LGE was significantly correlated with impairment of systolic function (Rho CC=0.395; p<0.001). For detection of systolic impairment, a critical value of end-systolic-volume (ESV)/LAA of ≥2.7 had an area under curve (AUC) of 0.902 (0.853–0.939), p<0.001; stroke-volume (SV)/LAA ≤3.0 had AUC=0.782(0.719–0.837), p<0.001, and end-diastolic volume (EDV)/LAA <7.4 had an AUC of 0.671 (0.602–0.735); p<0.001. In analyses of LGE, a value of SV/LAA of ≤3.0 had an AUC of 0.681 (0.612–0.744), p<0.001; while ESV/LAA and EDV/LAA were not significant (both p<0.05). ESV/LAA was correlated with systolic dysfunction (Rho-correlation-coefficient: 0.688; p<0.001) and existence of linear midventricular LGE stripe (Rho-CC=0.446; p<0.001). CONCLUSIONS: ESV/LAA was the most effective for detection of systolic impairment and was associated with the existence of LGE. Prospective validation for clinical applicability and prognostic relations are warranted in future studies.